Pengaruh Gaya Kepemimpinan Dan Kompetensi Kepala Sekolah Terhadap Kinerja Guru Sma Negeri Se Kabupaten Lombok Tengah - Wildan, Wildan (Jurnal Ilmiah Mandala Education (JIME), 2022)
The principal as a leader plays a role and is responsible for organizing, monitoring, fostering and improving the teaching and learning process. The concepts of leadership style and competence have a significant role in improving teacher performance. This quantitative research was conducted to determine: First: The effect of leadership style on teacher performance; Second: The influence of principal's competence on teacher performance; Third: The influence of leadership style and principal's competence on teacher performance. Data on leadership style, competence and teacher performance were collected using a questionnaire technique using a questionnaire instrument with a Likert scale. Data were analyzed by descriptive and inferential statistics using multiple regression at the 5% level. The results of data analysis show that (1) there is an effect of the principal's leadership style on teacher performance with the results of a significance value (<0.05) with a magnitude of 0.019 with a percentage of 67.5%, while the highest percentage of the type of democratic leadership style is 67.9% ( 2) there is an effect of principal competence on teacher performance, with the results of a significance value (<0.05) which has a magnitude of 0.001 with a percentage of 69.9%, (3) there is an influence of leadership style and principal competence on teacher performance with the results of the F test which has the magnitude of the significance value (<0.05) is 0.002. The magnitude of the influence of leadership style and principal's competence on teacher performance is 70.3% the rest is influenced by other variables. The implication of the research is the need for skills in acting to increase competence to the maximum and increase teacher performance, without forgetting other factors that also affect performance. teacher.